2022
DOI: 10.1021/acsami.2c08239
|View full text |Cite
|
Sign up to set email alerts
|

Nanodelivery System Alters an Insect Growth Regulator’s Action Mode: From Oral Feeding to Topical Application

Abstract: Insect growth regulators (IGRs) guide animal development through injection, oral feeding, or topical application. Among them, lufenuron is a widely used insect cuticle inhibitor but only shows a gastric toxic effect. Lacking contact toxicity limits the effective utilization when spraying the lufenuron pesticide. To overcome this shortcoming, a nanocarrier (star polycation, SPc)-based transdermal delivery system was applied to improve the penetrability and contact toxicity of lufenuron. The fluoride groups in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…We have shown that the nanometerization of various pesticides by SPc results in enhanced toxicity against pests in both laboratory experiments and field tests [ 13 21 , 88 , 89 ]. SPc shows great potential as pesticide adjuvant for large-scale application in the crop fields, and our biotoxicity analysis could help to develop guidelines to reduce the environmental and health risks.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the nanometerization of various pesticides by SPc results in enhanced toxicity against pests in both laboratory experiments and field tests [ 13 21 , 88 , 89 ]. SPc shows great potential as pesticide adjuvant for large-scale application in the crop fields, and our biotoxicity analysis could help to develop guidelines to reduce the environmental and health risks.…”
Section: Discussionmentioning
confidence: 99%
“…According to the previous interpretation of ITC data ( Ross and Subramanian, 1981 ), the self-assembly of calcium glycinate/SPc complex was through hydrogen bond and Van der Waals force, and this interaction was automatic. The complexation of SPc with exogenous substance can be achieved via different interaction forces, such as electrostatic interaction with thiamethoxam ( Yan et al., 2021a ) and lufenuron ( Zhang et al., 2022b ), hydrogen bond and Van der Waals force with chitosan ( Wang et al., 2021 ) and dinotefuran ( Jiang et al., 2022a ), and hydrophobic association with thiocyclam ( Wang et al., 2022b ). Thus, the application area of SPc is broad for delivering various types of exogenous substances.…”
Section: Discussionmentioning
confidence: 99%
“…The SPc-based nano-delivery system can reduce the particle size of synthetic/botanical pesticides and increase their water solubility and dispersity ( Yan et al., 2021b ; Yan et al., 2022 ; Wang et al., 2022b ). At the cellular level, the SPc can activate the clathrin-mediated endocytosis for enhanced cellular uptake and promote the endosomal escape for intracellular spreading of exogenous substances ( Wang et al., 2021 ; Ma et al., 2022b ; Yang et al., 2022 ; Zhang et al., 2022b ). In vivo , the SPc can increase plant uptake to improve the bioactivity of various exogenous substances ( Wang et al., 2022b ; Jiang et al., 2022a ; Jiang et al., 2022b ).…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated that the control e cacy can be improved by co-delivering dsRNA and pesticides, and codelivery of dsCDA1 and lufenuron may achieve a desired control e cacy for fall armyworms (Zhang et al 2022).…”
Section: Declarations Ethical Approvalmentioning
confidence: 99%